Климатипы сосны обыкновенной из южных районов Сибири в географических культурах в Западном Забайкалье - Новикова, Т.Н. (Фактори експериментальної еволюції організмів, 2013)
Aim. The aim of this study is the analysis of survival and growth of Scots pine climatypes

from forest-steppe regions of the Southern Siberia. Methods. Measurement of linear and radial increase of different Scots pine climatypes and revealing of their dependence on climatic factors. Results. In the region of our trial (West Zabaikalye) where moisture is a limiting factor plants seasonal growth directly depends on the amount of precipitation in May-June of the growing season. Conclusions. Some climatypes are resistant to environmental stress. Along witth the highly productive climatypes, they are of great importance in practical breeding.

Key words: Scots pine, climatypes, provenances,West Zabaikalye.